VvBAP1, a Grape C2 Domain Protein, Plays a Positive Regulatory Role Under Heat Stress - Ye, Qing; Yu, Jintao; Zhang, Zhen; Hou, Lixia; Liu, Xin (Frontiers in Plant Science, 2020)
Temperature is considered one of the critical factors directly influencing grapevine during the three primary growth and development stages: sprout, flowering, and fruit-coloring, which is strongly correlated to the yield and quality of the grape. The grapevine is frequently exposed to high-temperature conditions that are detrimental to growth. However, the mechanisms of the heat stress response and adaptation in grapevine are not adequately studied. The Arabidopsis copine gene AtBON1 encodes a highly conserved protein containing two C2 domains at the amino terminus, participation in cell death regulation and defense responses. Previously, we showed that a BON1 association protein from the grapevine, VvBAP1, plays a positive role in cold tolerance. Similarly, the involvement of VvBAP1 in the resistance to heat stress was also found in the present study. The results indicated VvBAP1 was significantly induced by high temperature, and the elevated expression of VvBAP1 was significantly higher in the resistant cultivars than the sensitive cultivars under heat stress. Seed germination and phenotypic analysis results indicated that overexpression of VvBAP1 improved Arabidopsis thermoresistance. Compared with the wild type, the chlorophyll content and net photosynthetic rate in VvBAP1 overexpressing Arabidopsis plants were markedly increased under heat stress. At high temperatures, overexpression of VvBAP1 also enhanced antioxidant enzyme activity as well as their corresponding gene transcription levels, to reduce the accumulation of reactive oxygen species and lipid peroxidation. Besides, the transcriptional activities of HSP70, HSP101, HSFA2, and HSFB1 in VvBAP1 overexpressing Arabidopsis plants were significantly up-regulated compare to the wild type. In summary, we propose that VvBAP1 may play a potential important role in enhanced grapevine thermoresistance, primarily through the enhancement of antioxidant enzyme activity and promoted heat stress response genes expression.